2016
DOI: 10.1027/1866-5888/a000165
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Trust in Supervisor, Turnover Intentions, and Voluntary Turnover

Abstract: Abstract. This study investigated the mediating effect of on-the-job embeddedness on the relationship between trust in supervisor and turnover. Survey data were collected among 471 employees of a restaurant chain in Indonesia. Results showed that job embeddedness mediated the relationship between trust in supervisor and turnover intentions. Turnover intentions were positively correlated with actual voluntary turnover 15 months later. The results confirmed that the trustworthiness of supervisors affects the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Based on the premise of Coleman (2001), recent empirical studies support the idea of high-performance work practices (HPWPs) (Combs et al, 2006) and trust in supervisor (TIS) (Purba et al, 2016) as important antecedents of reducing turnover intention (TI) in frontline employees. Human resource management (HRM) practices that its theorists consider as onthe-job performance enhancers are placed under HPWPs.…”
Section: Ijchm 303 1436mentioning
confidence: 99%
“…Based on the premise of Coleman (2001), recent empirical studies support the idea of high-performance work practices (HPWPs) (Combs et al, 2006) and trust in supervisor (TIS) (Purba et al, 2016) as important antecedents of reducing turnover intention (TI) in frontline employees. Human resource management (HRM) practices that its theorists consider as onthe-job performance enhancers are placed under HPWPs.…”
Section: Ijchm 303 1436mentioning
confidence: 99%
“…The attachment occurs because of individuals' compatibility with their organization, community and work environment. The impact of job embeddedness is that it can increase trust relationships with supervisors or superiors (Purba, Oostrom, Born, & van der Molen, 2016). Particularly, in Indonesia, employees' trust in supervisors is important for social identification.…”
Section: Job Embeddednessmentioning
confidence: 99%
“…A relationship attachment can increase the trust between superior and subordinate (Purba et al, 2016). Purba et al shows that the feeling of trust to superiors is positively and significantly related to on-thejob relationships.…”
Section: Job Embeddedness and Turnover Intentionmentioning
confidence: 99%
“…The reasons to examine JE are manifold. First, studies (Purba, Oostrom, Born, & van der Molen, 2016) have demonstrated that JE can reduce turnover. Second, trust in supervisors (TIS) (Goris, Vaught, & Pettit, 2003) and high performance work practices (HPWPs) (Combs, Liu, Hall, & Ketchen, 2006) are on-the-job aspects, and they are more likely related with JE within the organization.…”
Section: Introductionmentioning
confidence: 99%